Agama dan Kebahagiaan : A Literatur Review - Sulthon Nur Risky; Rahma Rosaliana Saraswati; Ratna Puspitasari (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2018)
This study aims to determine the relationship between happiness and religion. This research uses descriptive qualitative research method, with data collection techniques of literature review. The data taken from literature that focuses on the concept of true happiness. From this research obtained; the concept of ultimate happiness, not only the mere happiness of the world but also the happiness of the afterlife. In addition, to achieve the ultimate concept of happiness, it needs to be based on religion. The religion is a blend of faith, islam, and ihsan. Therefore, to achieve ultimate happiness we must follow the ways that God has set.